Development of Laboratory Virtual Learning Media on Alkene Submaterial - Jovita Tia Br Pakpahan; Marham Sitorus; Manihar Situmorang; Ratu Evina Dibyantini; Marudut Sinaga (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aims to develop virtual laboratory learning media for the alkenes subtopic and determine the feasibility, practicality, and effectiveness of its use in chemistry learning. This study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study was conducted in the Chemistry Education Study Program, State University of Medan, with students from class PSPK 25 C as the experimental class and class PSPK 25 E as the control class. The research instruments consisted of validation sheets from media experts and material experts, student response questionnaires, and learning outcome tests in the form of pretests and posttests. Data were analyzed descriptively quantitatively using percentages and N-Gain calculations. The results showed that the virtual laboratory media achieved a media feasibility percentage of 83.93% and a material feasibility percentage of 83.67%, categorized as very feasible. The media's practicality level reached 86.24%, categorized as very practical. The effectiveness test results showed that the experimental class achieved an N-Gain score of 0.80, categorized as high, while the control class achieved an N-Gain score of 0.67, categorized as moderate. Based on the research findings, the developed virtual laboratory media is effective for learning the alkenes subtopic.